2021
DOI: 10.1038/s41598-021-87825-4
|View full text |Cite
|
Sign up to set email alerts
|

A study of dopant incorporation in Te-doped GaAsSb nanowires using a combination of XPS/UPS, and C-AFM/SKPM

Abstract: We report the first study on doping assessment in Te-doped GaAsSb nanowires (NWs) with variation in Gallium Telluride (GaTe) cell temperature, using X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), conductive-atomic force microscopy (C-AFM), and scanning Kelvin probe microscopy (SKPM). The NWs were grown using Ga-assisted molecular beam epitaxy with a GaTe captive source as the dopant cell. Te-incorporation in the NWs was associated with a positive shift in the binding ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…The binding energy of Fe 2p 3/2 of pure α-Fe 2 O 3 is reported to be at 709.32 eV . The binding energy of Fe 2p 3/2 in TF-800 appeared at 711.95 eV, suggesting a decrease in the electron concentration at α-Fe 2 O 3 of TF-800 . The degree of delocalization and/or electronic coupling between TiO 2 empty electronic states can be demonstrated by proving that α-Fe 2 O 3 impacts electronic states around the Fermi level .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The binding energy of Fe 2p 3/2 of pure α-Fe 2 O 3 is reported to be at 709.32 eV . The binding energy of Fe 2p 3/2 in TF-800 appeared at 711.95 eV, suggesting a decrease in the electron concentration at α-Fe 2 O 3 of TF-800 . The degree of delocalization and/or electronic coupling between TiO 2 empty electronic states can be demonstrated by proving that α-Fe 2 O 3 impacts electronic states around the Fermi level .…”
Section: Resultsmentioning
confidence: 95%
“…20 The binding energy of Fe 2p 3/2 in TF-800 appeared at 711.95 eV, suggesting a decrease in the electron concentration at α-Fe 2 O 3 of TF-800. 112 The degree of delocalization and/or electronic coupling between TiO 2 empty electronic states can be demonstrated by proving that α-Fe 2 O 3 impacts electronic states around the Fermi level. 113 As a result of the low electron density at iron-based species, photogenerated electrons are readily taken up by TiO 2 , resulting in the production of • O 2 – , which degrades MB as proposed by the mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The work function ( Φ ) was extracted from the difference between the energy of the UV photons and the secondary electron cutoff (high binding energy 21.2 eV). 64 The calculated work functions ( Φ ) of N-GC and CoFe-800 are 4.86 and 4.99 eV, respectively. Therefore, the Fermi levels of N-GC-800 and CoFe-800 are −4.86 and −4.99 eV.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies have already demonstrated the successful incorporation and activation of Te dopants in GaAs NWs using a combination of atom probe tomography, Raman spectroscopy, photoluminescence, secondary ion mass spectrometry, electron holography, single NW transport measurement and Kelvin probe force microscopy [19][20][21][22]. Electron concentrations up to the 10 19 cm −3 range without compensation have been reported by Orr et al [21], while more recently concentrations between 2 and 4 x 10 19 cm −3 have also been reported for Te-doped GaAsSb NWs, using for the first time a combination of XPS/UPS and C-AFM/KPFM [23]. From the XPS spectra, signs of complex dopant distribution in the Te-doped GaAsSb NWs were observed but the latter could not be quantified using the above characterization techniques.…”
Section: Introductionmentioning
confidence: 92%